2022
DOI: 10.1097/iae.0000000000003529
|View full text |Cite
|
Sign up to set email alerts
|

Anomalies of Choroidal Venous Structure in Highly Myopic Eyes

Abstract: Purpose: To identify anomalies of choroidal venous structure in highly myopic (HM) eyes.Methods: Widefield indocyanine green angiographic images of 175 HM eyes (refractive error # -6.0D diopters or axial length .26.5 mm) and 100 control eyes taken between January 2014 and December 2018 were reviewed.Results: There were no significant differences in age and gender between HM patients and controls. Three types of changes of large choroidal veins were found in 103 HM eyes (58.86%): Asymmetry of vortex veins in 44… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 30 publications
(56 reference statements)
2
9
0
Order By: Relevance
“…Our findings, similar to those of Lu et al 1 demonstrated higher prevalence rates of choroidal venous anomalies in highly myopic eyes. The study highlights vortex vein asymmetry, large vortex vein branches in the macular area, and tapering distal ends in myopia.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…Our findings, similar to those of Lu et al 1 demonstrated higher prevalence rates of choroidal venous anomalies in highly myopic eyes. The study highlights vortex vein asymmetry, large vortex vein branches in the macular area, and tapering distal ends in myopia.…”
supporting
confidence: 93%
“…We recently read the article by Lu H and colleagues, titled “Anomalies of choroidal venous structure in highly myopic eyes," which discusses the findings from their study using wide-field indocyanine green angiographic images of 175 high myopic patients. 1 We would like to commend the authors on their valuable research and share some observations from our study, which may complement their findings.…”
supporting
confidence: 53%
“…10 In addition, although PSVs, as the short posterior ciliary arteries they are believed to be, could feed the neovascular tissue, recent publications point at venous structures as a new factor that could influence the balance of these lesions and thus mCNV activity. The asymmetry of choroidal venous patterns was reported by Mori back in 2004, 18 and a recent publication by Lu et al 19 describes the presence of three different types of large choroidal veins that can be found even in the absence of mCNV. But different groups have reported the presence of dilated subfoveal venous structures under the term DCVs.…”
Section: Discussionmentioning
confidence: 73%
“…15 The presence of these vessels was corroborated by Pedinielli et al, 8 in relation with marked variations of choroidal curvature in the posterior pole of HM eyes. 19 Since then, several authors have described different rates of PSV prevalence in cases diagnosed of mCNV that ranges from 70 to more than 90% 7,10,14 and offered different hypotheses regarding their potential role on the neovascular activity, from promoting the appearance of lacquer cracks to increasing the number of relapses and the need for antivascular endothelial growth factor injections as our group recently published. 10 In addition, although PSVs, as the short posterior ciliary arteries they are believed to be, could feed the neovascular tissue, recent publications point at venous structures as a new factor that could influence the balance of these lesions and thus mCNV activity.…”
Section: Discussionmentioning
confidence: 99%
“…Reprint requests: Kyoko Ohno-Matsui, MD, PhD, Department of Ophthalmology and Visual Science, Tokyo Medical and Dental University, 1-5-45 Yushima, Bunkyo-ku, Tokyo 1138510, Japan; e-mail: k.ohno.oph@tmd.ac.jp other abnormalities in the choroidal vasculature in PM eyes, such as asymmetrical distribution of the vortex veins, an isolated long vein that passed across the macula, and intervortex vein (IVV) anastomoses. 13 Intervortex vein anastomoses have been reported in many diseases, including pachychoroid spectrum diseases (PSD), [14][15][16] carotid cavernous sinus fistula, 17 and postscleral buckling surgery for a retinal detachment. 18 The imaging features of IVV anastomoses vary considerably in different diseases.…”
mentioning
confidence: 99%